Impedance measurements for determination of elastic and piezoelectric coefficients of films - Pardo, L.; Jiménez, R.; García, A.; Brebøl, K.; Leighton, Glenn J. T.; Huang, Zhaorong (Maney Publishing, 2010)
Most of those techniques used for the measurement of elastic coefficients for bulk piezoelectric ceramics are not applicable to films deposited on thick substrates because the measured properties, such as the resonant frequency, are usually dominated by the presence of the thick substrate. This work presents a preliminary study for the application of the automatic iterative method of Alemany et al. for the determination, from complex impedance measurements, of the film properties using a conventional self‐supported cantilever design used in microelectromechanical system applications and fabricated from a PZT thick film on a Si based substrat